Formation of colloidal nanocrystal clusters of iron oxide by controlled ligand stripping. Issue 1 (27th October 2015) - Fu, Junxiang; He, Le; Xu, Wenjing; Zhuang, Jianle; Yang, Xianfeng; Zhang, Xiaozeng; Wu, Mingmei; Yin, Yadong
Abstract : We report a "ligand stripping" method for the creation of secondary structures of colloidal nanocrystals. Abstract : We report a "ligand stripping" method for the creation of secondary structures of colloidal nanocrystals. Using iron oxide as an example, we demonstrate that the use of diols as "stripping agents" allows the controllable removal of the original capping ligands and induces aggregation of nanocrystals into well-defined clusters.